Understanding Equine Asthma and Recurrent Airway Obstruction (RAO) in the Horse - Amanda M. House (EDIS)
VM142, a 3-page fact sheet by Amanda M. House, describes this asthma-like condition in horses, how it is detected, and how it is treated. Includes references.